2014
DOI: 10.22260/isarc2014/0047
|View full text |Cite
|
Sign up to set email alerts
|

Safety Practices in the Lebanese Construction Market: Contractors’ Perspective

Abstract: The construction industry in the world is considered to be one of the most dangerous industries, claiming each year the lives of many workers. In particular, the boom in the construction industry in the Middle East over the past decades was accompanied with significant increase in death tolls and injuries among labor forces. Lebanon is a small developing country in the region who survived a harsh civil war that ended in 1990, and since then, its economy has become more dependent on the construction industry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Awwad studied the existence and extent of the application of safety practices by Lebanese contractors, management commitment to safety, and opportunities for enhancing safe practices [17]. Awwad collected the data through an interview questionnaire with Lebanese contractors and analyzed it using descriptive analyses.…”
Section: Related Construction Industry Safety Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Awwad studied the existence and extent of the application of safety practices by Lebanese contractors, management commitment to safety, and opportunities for enhancing safe practices [17]. Awwad collected the data through an interview questionnaire with Lebanese contractors and analyzed it using descriptive analyses.…”
Section: Related Construction Industry Safety Literaturementioning
confidence: 99%
“…Coordination and commitment of all levels of the construction workforce are vital to the success of any safety program and essential to facing any safety execution challenges in the construction industry [17]. Top management can enhance their safety programs by focusing on engineering improvements to equipment, methods, and materials and changing human behavior positively through education and training.…”
mentioning
confidence: 99%
“…Reference Findings [5,6] • The size of the contracting firm and the implementation of Safety and Health Management Systems (SHMS) are correlated: only large sized contractors and half of the total number of medium and small sized ones adopt SHMS.…”
Section: Table 1 Summary Of Major Safety Studies On the Lebanese Cons...mentioning
confidence: 99%
“…For example, a survey of contractors found that the most common reason for the lack of adoption of safety systems in Lebanon is that such safety practices are not required by law, in spite of the existence of Decree No. 11958 of 2004 concerning regulations of safety and labour protection in the construction industry [10].…”
Section: Introductionmentioning
confidence: 99%